Tradisi Pembacaan Majmu' Syarif sebagai Media Internalisasi Nilai-Nilai Spiritual di Madrasah Jam'iyyah Mahmudiyyah - Sri Agustina; Aura Amelia Kanaya; Zaifatur Ridha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Religious traditions in Islamic educational institutions occupy a strategic position in shaping the spiritual character of students. One tradition that has developed at Madrasah Jam'iyah Mahmudiyah is the recitation of Majmu' Syarif, which is regularly practiced by students and teachers. This study aims to examine the role of the Majmu' Syarif recitation tradition as a medium for the internalization of spiritual values at the madrasah. A qualitative approach with descriptive methods was employed in this study. Data were collected through observation, interviews, and documentation involving teachers, students, and madrasah administrators. The findings indicate that the regular practice of Majmu' Syarif recitation does not merely serve as a means of spiritual guidance, but also produces observable changes in student behavior. These changes include greater discipline in attending religious activities, active participation in congregational worship, and the growth of mutual respect and solidarity within the school environment. Students also demonstrated an improved understanding of sincerity as a value and developed the habit of prayer in their daily lives. This activity further functions as an effective non-formal learning medium through direct practice and sustained habituation. The tradition of reciting Majmu' Syarif has been shown to make a concrete contribution to the internalization of spiritual values, as reflected in measurable shifts in students' attitudes and behavior within the madrasah environment.